ANALYSIS OF THE BUSINESS FEASIBILITY OF ESTABLISHING A STRATEGIC BUSINESS UNIT FOR NON-AIRCRAFT PRODUCTS AT PT DIRGANTARA INDONESIA (The Indonesian Journal of Business Administration, 2019)
Company has to try to manage resources effectively and efficiently. It is intended to get more revenue, so that the company can be going concern. It will boost company to reach competitive levels. PT. DI, one of the Industry Strategies of BUMN, produces not only aircraft but also non-aircraft that have a contribution to company's overall revenue. Production process management of non-aircraft products must have good management. Researcher proposed to establish of a strategic non-aircraft products business unit. Researcher collects and processes data as a basic to make decision to establish strategic business unit for non-aircraft products. Researcher uses SWOT analysis, financial feasibility analysis, sensitivity analysis to provide recommendation to establish non-aircraft product business unit. The results of the analysis of the researcher are :Based on the SWOT Analysis of the proposed Non-Aircraft Products SBU for market & marketing aspects, HR, and Production and Facilities Aspects, PT. DI needs to minimize weaknesses and take opportunities. Through the establishment of Non-Aircraft Products SBUs, this will be implemented.Based on financial feasibility analysis, non-aircraft products SBU has NPV of IDR55.075.788.717 for 5 years. The IRR value is 27.20 % which means it is greater than WACC (17.24), so this business is feasible because it has the ability to get high returns. Net B/C ratio of 1.02 which means that every IDR1.00 in costs incurred will provide a profit of IDR0.02.Sensitivity analysis with two condition : 1) Assumed by material increase 5 % ; 2) Assumed by sales condition decrease 10 %. Based on sensitivity analysis assumed by material increase 5%, this project has NPV IDR37.827.291.229,61, IRR value is 19,28%, B/C ratio value is 1,00 its mean non-aircfraft products SBU is still feasible to implement. Based on sensitivity analysis assumed by material decrease 10%, this project has NPV IDR40.983.886.068,26, IRR value is 20,77 %, B/C ratio value is 1,00 its mean non-aircraft products SBU is still feasible to implement. Keyword : resources, non-aircraft product, SWOT analysis, feasibility, sensitivity analysis.